Emerging Promise of Cannabinoids for the Management of Pain and Associated Neuropathological Alterations in Alzheimer’s Disease - Uddin, Md. Sahab; Mamun, Abdullah Al; Sumsuzzman, Dewan Md.; Ashraf, Ghulam Md; Perveen, Asma; Bungau, Simona G.; Mousa, Shaker A.; El-Seedi, Hesham R.; Bin-Jumah, May N.; Abdel-Daim, Mohamed M. (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is an irreversible chronic neurodegenerative disorder that occurs when neurons in the brain degenerate and die. Pain frequently arises in older patients with neurodegenerative diseases including AD. However, the presence of pain in older people is usually overlooked with cognitive dysfunctions. Most of the times dementia patients experience moderate to severe pain but the development of severe cognitive dysfunctions tremendously affects their capability to express the presence of pain. Currently, there are no effective treatments against AD that emphasize the necessity for increasing research to develop novel drugs for treating or preventing the disease process. Furthermore, the prospective therapeutic use of cannabinoids in AD has been studied for the past few years. In this regard, targeting the endocannabinoid system has considered as a probable therapeutic strategy to control several associated pathological pathways, such as mitochondrial dysfunction, excitotoxicity, oxidative stress, and neuroinflammation for the management of AD. In this review, we focus on recent studies about the role of cannabinoids for the treatment of pain and related neuropathological changes in AD.